Controlling the Interaction of Light with Polymer Semiconductors. (15th July 2013) - Hellmann, Christoph; Paquin, Francis; Treat, Neil D.; Bruno, Annalisa; Reynolds, Luke X.; Haque, Saif A.; Stavrinou, Paul N.; Silva, Carlos; Stingelin, Natalie
Abstract : In this study, a generally applicable strategy is described to manipulate the optical properties of a wide range of polymer semiconductors in the solid state. Blending these materials with a non‐conjugated, polar polymer matrix is found to be the processing key to a drastic change and red‐shift of the absorption characteristics.